(untitled) (Conference on English Language Teaching, 2023)
Expressing emotions, share information, and convey messages, communication is a crucial part of human life. Successful communication depends on understanding what speakers intend when they communicate and figuring out the meaning of each phrase used in an utterance. In the delivery of language to the society, there are important elements that influence the language when used. One of the elements is Reference. This study examined the pragmatic references used in this Netflix series "Squid Game". The Netflix original series "Squid Game" is being watched by millions of people all over the world. It tells the tale of a group of adults who are heavily in debt and who struggle to win prize worth billions of Won (the official currency of South Korea) with their lives on the line. There are two objectives of this research; 1) to identify the types of deixis used in the utterances in the series squid game; and 2) to explain the references of using deixis found in the movie. The method used in this research is qualitative descriptive method because the data were analyzed in the form of words and utterances. The theory used in this research is Deixis theory by Stephen C. Levinson’s, also supported theory of references by Yule. Based on the data deixis that have been found and analyzed by the researcher in this research, person deixis is more dominant used in the novel, and for the use of references, anaphora reference is more dominant used than cataphora reference in the novel the Netflix series squid game.